Student Discipline Problems and the Role of Counselors and School Principals to Overcoming Them - Fitri, Hamidah; Marjohan, Marjohan; Alizamar, Alizamar (Jurnal Aplikasi IPTEK Indonesia, 2021)
Violations that often occur in school are disciplinary violations committed by students. Discipline problems are problems which, if not resolved quickly, will have an impact on the smoothness of the learning process in the classroom. Some of the personnel who play a role in overcoming discipline problems in schools are counselors and school principals. This research is a library research, by searching, reading, studying, and analyzing the content of books and supported by various literature related to them. Based on the research results, it can be concluded that school counselors and school principals play an important role in overcoming student discipline problems. In addition, cooperation with other school personnel is needed to overcome disciplinary problems that occur.